The historical market for technology licenses: chemicals, pharmaceuticals, and electrical engineering in imperial Germany - Carsten Burhop; Thorsten Lübbers (Max Planck Institute for Research on Collective Goods, 2009)
We investigate a sample of 180 technology licensing contracts closed by German chemical, pharmaceutical, and electrical engineering companies between 1880 and 1913. A regression analysis shows that licensing contracts closed before a patent was granted and contracts closed between firms and individual inventors had a higher probability of including a profit-sharing clause. This supports Jensen and Thursby's (2001) model, who propose equity-sharing licensing contracts to solve moral hazard problems. Moreover, we show that milestones were a substitute for profit shares. Furthermore, exclusive licences offered a significantly higher profit share to the licensor.
Keywords: N83; O32; L14; 330; Economic History; Germany; pre-1913; Licensing contracts; Technology transfer